Strategi Keberlanjutan Subak di Desa Jatiluwih Kabupaten Tabanan - I Gde Agus Adnya Widagda; I Putu Arya Dharmayasa (Universitas Pendidikan Ganesha, 2025)
This study aims to identify (1) the factors influencing the sustainability of the Subak system in Jatiluwih Village, Tabanan Regency, and (2) the strategies that can be implemented to maintain its sustainability amidst modern challenges such as land conversion and the declining interest of younger generations in agriculture. This research employed a quantitative approach using data collection techniques including questionnaires, interviews, and documentation. The population consisted of 395 Subak Tempek members in Jatiluwih Village, with a sample of 135 respondents selected through proportional sampling. Data were analyzed using the MICMAC and SMIC-Prob Expert methods to identify key variables and formulate sustainability strategies. The results indicate that the sustainability of Subak is influenced by interconnected economic, social, and environmental factors, such as strengthening Subak institutions, policy support, utilization of environmentally friendly technology, and farmer empowerment through local product development. Effective Subak sustainability strategies involve collaboration among communities, the government, and other stakeholders to preserve this traditional irrigation system as a world cultural heritage that supports ecological balance and enhances the local economy.